Pengaruh Media Sosial Terhadap Perilaku Remaja - Saputra, Wawan; Islam, Fikril; Iswinarti, Iswinarti (Green Publisher Indonesia, 2025)
The use of social media has become an integral part of adolescents' lives, yet its impact on their behavior remains a subject of debate. This article aims to systematically review the existing literature on the influence of social media on adolescent behavior, utilizing the SPIDER and PRISMA methodologies. This study includes adolescents aged 12-18 years and examines various behavioral aspects, including social behavior, academic performance, and mental health. From 500 articles found in databases such as, Scopus, and Google Scholar, 14 articles were selected based on strict inclusion criteria. Excessive use of social media is often associated with decreased academic performance and mental health issues such as anxiety and depression. Support from parents, educators, and policymakers is crucial in promoting healthy social media usage among adolescents.